A histomorphological and immunohistochemical analysis of invasive lobular carcinoma of breast: A case series - Suchiang, Meera; Das, Gunabhi Ram; Dowerah, Swagata; Saikia, Julee; Rahman, Washima; Borgohain, Mondita; Gogoi, Gayatri (Asian Journal of Medical Sciences, 2024)
Invasive lobular carcinoma (ILC) is the second most common special subtype of invasive breast carcinoma comprising 5–15%. ILC defines as invasive carcinoma comprising non-cohesive single-file linear pattern in fibrous stroma. The aim of the study was to evaluate the histomorphological features and immunohistochemical analysis of ILC. A total of 19 cases were encountered from March 2020 to February 2024 out of 129 breast cancers. The sociodemographic profiles and clinicopathological parameters of the patients were studied with special emphasis on their morphology and hormone receptor status. The mean age of patients is 42.8 years. Out of 19 cases, 84.2% showed feature of classic type, 5.2% of tubule-lobular, and 10.5% of pleomorphic lobular carcinoma. The majority of cases (63.2%) showed histologic Grade 2, and 10.5% showed Grade 3. On immunohistochemistry examination, 79% were estrogen receptor (ER) and progesterone receptor (PR) positive with 10.5% of cases was human epidermal growth factor receptor 2/neu (HER2/neu) positive. Our study showed higher cases of classic type ILC, mostly of histologic Grade 2; higher ER-PR receptor positivity and HER2/neu negativity.